Tsunami understanding media: Android-physics mobile learning to improve problem solving-skills and natural disaster preparedness - Abdillah, Annas Jati; Mundilarto, Mundilarto; Sulaiman, Syazana (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This research aimed to determine the effectiveness of the implementation of tsunami understanding media through Android-based physics mobile learning in improving students' problem-solving skills and natural disaster preparedness. This study employed quasi-experiment research with a non-equivalent control group design. This research subjects were fifty-six students of class XI IPA at SMA N 1 Kretek, Bantul, Yogyakarta. The sampling technique employed in this research was the simple random sampling technique to determine the experimental and control groups.  The research data had been obtained through pretest and posttest in the form of essay tests. The data obtained were then analyzed using N-gain. The analysis results were used to determine the effectiveness of the media using the Hotelling's Trace test in MANOVA test analysis. Normally distributed and homogeneous data are required to perform the multivariate analysis. The results showed that the tsunami understanding media through Android-based physics mobile learning improved students' problem-solving skills and natural disaster preparedness compared to the learning using PowerPoint presentation. The research decisions were based on the significant value that was smaller than 0.05 (0.000<0.05), and the value of the Partial Eta Squared was 0.359 in the broad category.